Train-induced floor vibration and structure-borne noise predictions in a low-rise over-track building. (15th March 2022) - Tao, Ziyu; Moore, James A.; Sanayei, Masoud; Wang, Yimin; Zou, Chao
Highlights: Floor vibration and room noise predictions on upper floors of a building over a metro depot. Composite action significantly stiffens the bending rigidity of the girders. Coupling of bending waves in girders and floor transmits energy from girders to floor. Good agreement between predicted and measured floor vibration and room noise. An efficient way, both in modeling and in computation, for predicting train-induced floor vibration and structure-borne noise. Abstract: Frequent train operations in metro depots can have adverse effects on the buildings' occupants in terms of feelable vibration and noise. A method is proposed to predict vibration transmissions from columns into girders and subsequently into the floors. This method is quite efficient in modeling and computation, saving engineers time and computational cost. It is highly useful in the design phase for identifying undesirable feelable vibration and audible noise within buildings and for developing mitigation measures that improve human comfort, operation of sensitive equipment, and manufacturing. Train-induced ground-borne vibration in metro depots transmits into the upper floors of over-track buildings primarily through axial waves in the supporting columns. The vertical vibration of a column at a floor inputs mechanical power into the attached girders based on their impedance at the column. An analytical model of the girder impedance is developed that accounts for the coupling to the floor and for composite action where in-plane deformation in the floor stiffens the girder. Along with the measured vibration velocity levels at the columns, impedances of the coupled floor and girders are used to predict the mechanical power input at individual columns into the girders. The input mechanical power generates bending waves in the girders with subsequent transmission out into the attached floor along their length. The resulting average floor vibration levels in the bay are predicted in response to the total mechanical power input, which in turn radiate noise from the floor structure into the room. The overall model from vibration inputs at the columns to room noise levels was applied to a 4-story over-track building during train passbys under the building in the Qianhai Metro Depot in Shenzhen, China. The predicted average floor vibration levels and room noise levels were in good agreement with their corresponding measurements.